SOSIALISASI PENANGANAN SAMPAH RUMAH TANGGA DI DESA BOLA - Marlina Elsanti; Theresia Maria Cita Suci (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
The behavior of throwing garbage anywhere causes air pollution and various diseases. Disposing of garbage directly around the house or at school has become a community habit. as the population increases, the amount of waste increases and accumulates so that this problem can be resolved requires serious handling so that the purpose of this activity is to provide socialization about handling household waste. implementation is carried out by providing socialization to the community and practice in the homes of the village residents. the results of the activities show that the implementation of the fourth pillar STBM program has been carried out well by the health office and the village government and has monitored and evaluated with verification the implementation of the program for the procurement of healthy trash bins for the community